2020
DOI: 10.1186/s12889-020-08885-1
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of factors associated with unmet need for family planning among Malawian women

Abstract: Background Malawi has a high fertility rate which is also characterized by a relatively high prevalence of unmet need for contraception. However, little is known about the influence of individual- and community- level characteristics on unmet need in Malawi. This study examined the individual- and community- level factors associated with unmet need for family planning (FP) among Malawian women. Methods Data from the 2015–16 Malawi de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 26 publications
21
29
2
Order By: Relevance
“…54 In this regard, a systematic metaanalysis conducted in Ethiopia revealed that the odds of unmet need for FP were 2.3 times higher among women with age at first marriage <18 years than women marriage at 18 years and above. 60 Similar to a study conducted in Malawi, 10 this study found that unmet need for FP was greater among women who cited the distance to a health facility as a problem. This finding suggests improving geographical access to health facilities decreases unmet need for FP.…”
Section: Open Accesssupporting
confidence: 71%
See 4 more Smart Citations
“…54 In this regard, a systematic metaanalysis conducted in Ethiopia revealed that the odds of unmet need for FP were 2.3 times higher among women with age at first marriage <18 years than women marriage at 18 years and above. 60 Similar to a study conducted in Malawi, 10 this study found that unmet need for FP was greater among women who cited the distance to a health facility as a problem. This finding suggests improving geographical access to health facilities decreases unmet need for FP.…”
Section: Open Accesssupporting
confidence: 71%
“…This is consistent with a study conducted in Malawi. 10 The result of our study further reveals that women who live in communities with high media exposure had decreased odds of unmet need for FP compared with women in low-media exposure communities. This Open access might be due to educated women having higher odds of understanding health messages and experiencing demand for FP services.…”
Section: Open Accesssupporting
confidence: 55%
See 3 more Smart Citations